Efferocytosis by macrophages in physiological and pathological conditions: regulatory pathways and molecular mechanisms - Sheng, Yan−Ran; Hu, Wen−Ting; Chen, Siman; Zhu, Xiao−Yong (Frontiers in Immunology, 2024)
Efferocytosis is defined asthe highly effective phagocytic removal of apoptotic cells (ACs) undertaken by professional phagocytes or non-professional phagocytes.Tissue-resident professional phagocytes ("efferocytes"), such as macrophages, have high phagocytic capacity and are crucial to resolve inflammation and aid homeostasis. Recently, numerous exciting discoveries have revealed some divergent (and even diametrically opposite) findings regarding on the metabolic immune reprogramming associated with efferocytosis by macrophages. In this review, we highlight the key metabolites involved in during the three phases of efferocytosis and immune reprogramming of macrophages in under physiological and pathological conditions are highlighted. The next decade is promising expected to yield further breakthroughs in the regulatory pathways and molecular mechanisms connecting immunological outcomes to metabolic cues, as well as avenues for "personalized" therapeutic intervention.